Conjugated polymers : properties, processing, and applications - Reynolds, John R., 1956-; Thompson, Barry C.; Skotheim, Terje A., 1949- (Handbook of conducting polymers., 2019)
This book covers properties, processing, and applications of conducting polymers. It discusses properties and characterization, including photophysics and transport. It then moves to processing and morphology of conducting polymers, covering such topics as printing, thermal processing, morphology evolution, conducting polymer composites, thin films